Kedudukan Hak Cipta Sebagai Hak Kebendaan dan Eksekusi Jaminan Fidusia Atas Hak Cipta - Andini Setiani Umar (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2024)
This paper examines whether or not copyright(s) can be used as collateral in a credit facility. To answer this question, there are two major issues to consider. First, we must determine whether copyright(s) is a property right, and if so, whether copyright(s) can be used as collateral. So, what mechanism can we use to ensure copyright(s)? Our research shows that copyright(s) are property rights that can be used as collateral in a credit facility via fiduciary guarantee; Second, because we established that copyright(s) are property rights that can be used as collateral in a credit facility via fiduciary guarantee. The next step is to determine how we can secure and execute copyright(s) as collateral. Our research shows that the main procedure can be found in Law Number 42 of 1999 on Fiduciary and Law Number 24 of 2019 on Creative Economy.